Gestos e fala nas narrativas infantis - Brandão, Soraya Maria Barros de Almeida (2015)
The present study aims to observe the course of oral language acquisition in its multi-system in children's stories genre, that is, to describe how the acquisition has come about observing the orality in its multi-system: gestures and speech in order to realize the importance of gestures in the discursive construction. For this, we have conducted a longitudinal research having as subject 6 (six) children from early childhood education, from 2 (two) to 5 (five) years old, in which 4 (four) of them male and 2 (two) female. A municipal day care center located in the city of Campina Grande-PB was the place selected for the study. Data were collected during six months, from the thirteenth of March, 2013 to the Twenty-third of August, 2013, precisely once a week, from records written by the researcher, as well as recordings in the camcorder. There were 55 filming sessions, representing an average of 2h 2min 53s hours, considering that each child tell more than one story. For analytical purposes, only the story of Little Red Riding Hood was considered, since children, mostly, showed more interest in this story. Thus, the sessions that built up this research corpus are in number of 12, totaling 24 min 04s. For research purpose, we analyze the multi-system in children's oral narratives productions in retelling stories situations. In data processing, we contemplate the development of the child's narrative discourse considering the discursive and gestural elements present in the speech. We have approached studies involving language acquisition in our theoretical trajectory, considering as background for this research the socio-interactive bases, supported by Tomasello (2003), Bruner (1983, 1997), Vygotsky (1991, 2005) Cavalcante (1994, 1999, 2003, 2010), Faria (2002, 2004), Del Ré (2006), Del Ré, Paula e Mendonça (2014a, 2014b), among others. In addition, we have conducted a study on orality multi-system: gestures and speech based on McNeill (1974, 1985, 1992, 2000) and Kendon (1981, 2000). Studies on children's narratives were also addressed in this research based on Perroni (1992), François (1996, 2009) and Bruner (1997, 1998, 2001). We have assumed that construction of narrative discourse by young children is by interaction with others, with gestures as intrinsic elements in the narrative process. From this perspective, the gestures compose the linguistic assisting in the narrative construction, thus having a crucial role in structuring oral speech, which was observed in our data. The results point that in every scene, having or not a language proficiency, children have narrative competence. A competence that goes from the holophrastic statement to the narrative autonomy, in a movement that interweaves voices and gestures forming a whole discourse. Thus, the child, since childhood, here shown from two years, two months and eighteen days (2;2:18), already constituted as narrator, since relying on multimodal elements and under the supervision of the researcher can weave the narrative thread, in a discursive movement that mixes gestures and speech.